Atypical Rett syndrome in a girl with mosaic triple X and MECP2 variant - Satoru Takahashi; Ryo Takeguchi; Mami Kuroda; Ryosuke Tanaka (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Rett syndrome (RTT) is a neurodevelopmental disorder that predominantly affects girls, resulting from a loss‐of‐function variant in X‐linked MECP2. Here, we report a rare case of a girl with RTT with an X chromosome mosaic karyotype (46,XX/47,XXX). Methods Fluorescent in situ hybridization (FISH) was carried out to confirm the mosaic karyotype. Sanger sequencing was carried out to genetically diagnose RTT. Furthermore, we assessed the X chromosome inactivation (XCI) pattern. MECP2 expression levels were examined via RT‐PCR. Results The patient presented with preserved speech variant, the milder form of RTT. Genetic examination revealed a de novo, heterozygous, truncating variant of MECP2. FISH revealed mosaicism in the 47,XXX karyotype in 6% of her cells. The XCI assay revealed unbalanced inactivation with skewing in favor of the paternal X chromosome. MECP2 was downregulated to only 84% of the control, indicating that the patient's variant was probably of paternal origin. Unbalanced XCI in this patient might have contributed to the alleviation of the phenotype. However, her supernumerary X chromosome was derived from maternal X chromosome harboring the wild‐type allele and might have had no preferential effect on her RTT‐related phenotype. Conclusion The present results indicate that phenotypic effects of X chromosome aneuploidy depend on the nature of the supernumerary X chromosome, the pattern of mosaicism, and XCI status.